Heatguard: An ultra-low-cost three-dimensional-printed sensor for skin temperature alert and reporting system. (May 2019) - Li, Rui; Smith, Aaron; Tadinada, Harshitha; Hovet, Sierra; Tse, Zion Tsz Ho
A heatstroke is one of the most serious forms of heat injury and is classified as a medical emergency. It is characterized by an elevated core body temperature along with the failed body cooling mechanism in response to the sudden heat-up. People vulnerable to a heatstroke are children, elders and sports professionals. Previous efforts have emphasized exercise adjustments and post-treatments, such as environmental-based activity modification and cold-water immersion. However, the general public, especially elders, will have difficulty to conduct such adjustments by themselves. Moreover, few studies have been conducted on the early preventive measurement stage. A wearable three-dimensional-printed thermochromic device proposed here can warn the people of a sudden rise in skin temperature and can advise them to take quick action. Combined with the smartphone applications, for both the android and iPhone platform, the device is able to monitor real-time skin temperature and alerts the people who are vulnerable to a heatstroke. The three-dimensional printable resin developed can change color at a specific activation temperature. The device has undergone a series of performance tests in order to optimize the color transition rate and stability of color change. The accuracy of our device is compared to the conventional thermometer; the regression analysis shows the R 2 value is 0.7599 and the average error is 1.3 °C. Future work will be to mitigate the surrounding lighting effects on the smartphone camera and further improve our device accuracy.